(untitled) (World Science, 2020)
The article describes the process of video materials’ criteria selection for building pre-service food technologist’s speech production competence and the procedure of video materials selection according to these criteria. The article defines the definition of selection criteria and determines factors were considered in the process of video materials’ selection criteria specification.